Chemical Mapping by Macroscopic X‐ray Powder Diffraction (MA‐XRPD) of Van Gogh's Sunflowers: Identification of Areas with Higher Degradation Risk. Issue 25 (24th March 2018) - Vanmeert, Frederik; Hendriks, Ella; Van der Snickt, Geert; Monico, Letizia; Dik, Joris; Janssens, Koen
Abstract: The discoloration rate of chrome yellow (CY), a class of synthetic inorganic pigments (PbCr1− x S x O4 ) frequently used by Van Gogh and his contemporaries, strongly depends on its sulfate content and on its crystalline structure (either monoclinic or orthorhombic). Macroscopic X‐Ray powder diffraction imaging of selected areas on Van Gogh's Sunflowers (Van Gogh Museum, Amsterdam) revealed the presence of two subtypes of CY: the light‐fast monoclinic PbCrO4 (LF‐CY) and the light‐sensitive monoclinic PbCr1− x S x O4 ( x ≈0.5; LS‐CY). The latter was encountered in large parts of the painting (e.g., in the pale‐yellow background and the bright‐yellow petals, but also in the green stems and flower hearts), thus indicating their higher risk for past or future darkening. Overall, it is present in more than 50 % of the CY regions. Preferred orientation of LS‐CY allows observation of a significant ordering of the elongated crystallites along the direction of Van Gogh's brush strokes. Abstract : Sunflowers : In addition to the light‐fast chrome yellow subtype PbCrO4 (crocoite), light‐sensitive monoclinic PbCr1− x S x O4 ( x ≈0.5, LS‐CY) was found throughout several areas of Van Gogh's Sunflowers, thus identifying areas of the painting that are at risk of darkening. In addition, information on the orientation of LS‐CY pigment crystallites in Van Gogh's brush strokes were revealed.